Ionic liquids: promising solvents for halal industry - Elgharbawy, Amal A.M.; Azmi, Nor Azrini Nadiha; Hamzah, Mohd. Salleh (Rynnye Lyan Resources, 2020)
Replacement of volatile organic solvents with ionic liquids (ILs) in industrial applications is a concerned matter and a trending approach. ILs became the choice of solvents due to their merits such as low melting points (<100°C) and insignificant vapor pressure. Despite being expansively investigated, ILs have not been intensively reviewed as eco-friendly solvents for the halal industry, which is the concept of this mini review. ILs have been used as surfactants, extractants for the purification of biomolecules, stabilizers for enzymes and in biosensors applications. Regardless of the lack of data on the toxicity of food products with ILs residues, low doses of ILs in in vitro tests did not lead to cell damage. Moreover, several ILs have stabilizing effects on biomolecules such as enzymes and proteins. Thus, new applications of ILs in the halal industry are feasible within the concept of halalan tayyiban (lawful and safe, good, wholesome).